Sistem informasi Inventory Iparepart Motor Pada Bengkel Al Motor - Siregar, Fitri Rizky Wahyuni; Lubis, Ihsan; Maulana (CV. Hawari, 2023)
The development of information technology is growing so rapidly, making many people aware of the importance of information. At the AL motorcycle repair shop, the ongoing process is still not effective because the inventory data management is still using the manual method using Microsoft Excel which makes the process of searching for goods take quite a long time. Where sometimes it often happens that the data in the warehouse is wrong with the data in microsoft excel which makes the workshop party have to calculate the stock from the beginning again to match the data in microsoft excel with in the warehouse. The purpose of this research is to assist the workshop in recording stock which has been ineffective in terms of workmanship and the results of this study resulted in the application of this spare parts inventory information system to be a medium to increase accuracy in the suitability of data items with existing physical quantities.